Impurity Migration Pattern Simulated by Test Particle Module Under BOUT++ Framework (Communications in Computational Physics, 2019)
A test particle module is developed under BOUT++ framework. The guiding-center orbits in real divertor geometry can be calculated. The turbulence transport is implemented by random walk model. Impurity migration patterns under different turbulence transport levels are simulated by this module. As transport increase,migration pattern is modified significantly. More particles are lost and the lost at lowfield side boundary increase significantly.
Keywords: Impurity migration; test particle; BOUT++.